Kiat Pengolahan Pangan yang Tepat Sebagai Rahasia Anak Sehat Bebas Stunting - Ayuni, Suzila; Ismaniar, Ismaniar; Putri, Lili Dasa (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 25 No 1 (2025)DO - 10.24843/PJIIB.2025.v25.i01.p07, 2025)
This article reviews tips for correct food processing as the secret to healthy, stunting-free children. This article is motivated by survey results which state that the prevalence of stunting is high both in Indonesia and the world. At the global level, WHO estimates that 22.0% or 149.2 million children under five will be affected by stunting in 2020. Of this number, more than half are in Asia (53%). Therefore, food processing tips emerge as a promising solution to overcome these problems. This is often caused by a lack of correct understanding of food processing, which can hinder the optimal use of nutrients from available food. If food processing is done in the wrong way, the nutrients in the food can be reduced. This can cause nutritional changes in food and impact the child's growth. Therefore, education about how to process food so as not to damage its nutritional content is very important to prevent stunting. This research discusses three discussions, namely: (1) stunting in early childhood, (2) the right way to process food ingredients based on type, and (3) tips for local-based food processing for early childhood in preventing stunting. The source of this article collects data using the literature study method. This article highlights the importance of education in food processing to maintain nutritional quality and prevent stunting. By increasing understanding of the correct way to process food, it is hoped that it can make a significant contribution to efforts to prevent stunting.